Retrieval and Processing of Information with the Use of Multi-Agent System - Poniszewska-Maranda, Aneta; Gebel, Łukasz (Journal of Applied Computer Science, 2016)
Today the amount of information available in the world is so large that it exceeds significantly the perceptual capacity of a man. The progress of science and increased access to the media, in particular to the Internet, allows an increasing number of people to create and publish their own content. Refer to the information that can be found in our area of interest is limited to read a very small part of the works on the topic. What’s more the overlooked information can be very useful, but selective viewing of the contents and limited time resources prevent the users to meet their information needs. An attempt to solve this problem are multi-agent systems, using intelligent methods of retrieval and processing of information.